Comparable antibody levels in heterologous and homologous mRNA COVID-19 vaccination, with superior neutralizing and IgA antibody responses in mRNA homologous boosting - Salma, Younes (2024)
BackgroundPriming with two doses of AZD1222 (Oxford-AstraZeneca; ChAd) followed by a third mRNA vaccine boosting is considered in several countries, yet comparisons between heterologous and homologous booster efficacy remain unexplored. AimTo evaluate and contrast the immunogenicity of homologous and heterologous boosting regimens. MethodThe study examined antibody responses in 1113 subjects, comprising 895 vaccine-naïve individuals across different vaccination strategies (partial, primary series, heterologous booster, homologous booster) and 218 unvaccinated, naturally infected individuals. Assessments included neutralizing total antibodies (NTAbs), total antibodies (TAbs), anti-S-RBD IgG, and anti-S1 IgA levels. ResultsThe study found mRNA vaccines to exhibit superior immunogenicity in primary series vaccination compared to ChAd, with mRNA-1273 significantly enhancing NTAbs, TAbs, anti-S-RBD IgG, and anti-S1 IgA levels (p < 0.001). Both booster types improved antibody levels beyond primary outcomes, with no significant difference in TAbs and anti-S-RBD IgG levels between regimens. However, homologous mRNA boosters significantly outperformed heterologous boosters in enhancing NTAbs and anti-S1 IgA levels, with the BNT/BNT/BNT regimen yielding particularly higher enhancements (p < 0.05). ConclusionThe study concludes that although TAbs and anti-S-RBD IgG antibody levels are similar for both regimens, homologous mRNA boosting outperform heterologous regimen by enhancing anti-S1 IgA and neutralizing antibody levels.